Mitochondrial drug targets in neurodegenerative diseases. Issue 3 (1st February 2016) - Lee, Jiyoun
Graphical abstract: Abstract: Growing evidence suggests that mitochondrial dysfunction is the main culprit in neurodegenerative diseases. Given the fact that mitochondria participate in diverse cellular processes, including energetics, metabolism, and death, the consequences of mitochondrial dysfunction in neuronal cells are inevitable. In fact, new strategies targeting mitochondrial dysfunction are emerging as potential alternatives to current treatment options for neurodegenerative diseases. In this review, we focus on mitochondrial proteins that are directly associated with mitochondrial dysfunction. We also examine recently identified small molecule modulators of these mitochondrial targets and assess their potential in research and therapeutic applications.